Electoral rules, political competition and citizens’ participation in the Portuguese local elections, 1979–2009 - Freire, A.; Martins, R.; Meirinho, M. (Portuguese Journal of Social Science, 2012)
The main purpose of the present paper is to describe and explain the influence of the electoral rules, the type of elections and the patterns of political competition upon citizens’ participation and voting choice in the Portuguese local elections between 1979 and 2009. Using aggregate data with the county as our unit of analysis, we will test the impact of the electoral rules, bipartism (concentration of the vote and/or seats in the two major parties, although in the present article we use mainly concentration of the vote) and the pattern of political competition upon turnout. Additionally, we will also test the impact of the electoral rules, and the pattern of political competition upon the level of bipartism at the local level. Several other control variables are also considered. Using a similar model we will try also to explain the level of party competitiveness in each county. By and large, we show that local democracy, the level of party competitiveness and the presence of non-partisan lists boosts participation. However, district magnitude works contrary to our expectations: the smaller the district, the greater the participation. Thus, local democracy has more impact than electoral rules in this case. We also show that bipartism is positively associated with low levels of competitiveness, absence of non-partisan lists and absence of simultaneous government (i.e., of the same party in power at both local and national level). Competitiveness is boosted by the presence of simultaneous government. These findings are rather robust because they remain after controlling for several other variables.